ANALISIS HUKUM ADMINISTRASI TERHADAP KEBIJAKAN PERIZINAN FASILITAS KESEHATAN - Hotmaria Hertawaty Sijabat (CV. Adiba Aisha Amira, 2025)
Health facility licensing policies are crucial in ensuring the quality of health services and protecting the public. As an administrative legal instrument, licensing provides a regulatory framework for the management of health facilities in accordance with applicable standards. However, the implementation of these policies faces a number of challenges, such as bureaucratic complexity, lack of transparency, and inadequate oversight, which can hinder access to health services, particularly in remote areas. Furthermore, the risk of irregularities in the licensing process underscores the need for regulatory reform and oversight mechanisms. Therefore, administrative law reform based on the principles of transparency, efficiency, and accountability is essential to ensure a more responsive licensing system that supports the development of the national health sector. This study provides an administrative law analysis of health facility licensing policies to recommend solutions for improving the effectiveness of regulations in this field.